Evaluation culture and good governance: Is there a link?. (July 2019) - Dahler-Larsen, Peter; Boodhoo, Adiilah
An important motivation for the institutionalization of evaluation culture in countries around the world is the belief that accountability and transparency will thereby be enhanced. We subject this narrative about evaluation's contribution to good governance to empirical analysis. We also argue that the meaning and relevance of this general narrative differs across national contexts. We build on data from a systematic assessment of evaluation culture in 19 countries (Jacob et al., 2015), add one country using the same systematic approach, and combine these findings with an indicator of transparency in government provided by Transparency International. We find a positive correlation between evaluation culture and transparency, and discuss threats to a causal interpretation hereof. We go into depth with two particular countries at either end of the transparency scale. We argue that the meaning of the link between evaluation culture and transparency differs whether the chosen perspective is generally comparative or situated in particular national, historical, and political contexts. In countries where transparency is high already, there might be diminishing marginal returns on evaluation, at least regarding its contribution to accountability and transparency.